1996
DOI: 10.1055/s-2007-999026
|View full text |Cite
|
Sign up to set email alerts
|

Serine/Threonine Dephosphorylation May Be Involved in Tyrosine Phosphorylation: A New Mode of Signal Transduction in Platelets

Abstract: Platelet signal transduction involves not only reversible phosphorylation of proteins on both tyrosine and serine/threonine residues, but also mechanisms of cross-talk to coordinate different pathways. We have, therefore, investigated the effect of okadaic acid, a potent inhibitor of serine/threonine protein phosphatases type 1 and type 2A (PP1 and PP2A), to better understand the interplay that must exist between serine/threonine and tyrosine phosphorylations during platelet activation.Okadaic acid drastically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…First, how can inhibition of a Ser/Thr phosphatase (PP2Ac␣) activate a tyrosine kinase (Src)? While the occurrence of such a cross-talk has been widely accepted (24), the underpinning mechanisms are not clear. Inhibition of PP2Ac is likely to alter the Ser/Thr phosphorylation of multiple cellular proteins, including some that have the potential to regulate Src activity.…”
Section: Discussionmentioning
confidence: 99%
“…First, how can inhibition of a Ser/Thr phosphatase (PP2Ac␣) activate a tyrosine kinase (Src)? While the occurrence of such a cross-talk has been widely accepted (24), the underpinning mechanisms are not clear. Inhibition of PP2Ac is likely to alter the Ser/Thr phosphorylation of multiple cellular proteins, including some that have the potential to regulate Src activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports and our data have shown that serine/threonine phosphatase activities are needed for an agonist to initiate platelet secretion, aggregation and thromboxane synthesis, since okadaic acid, a potent inhibitor of PP1 and PP2A, inhibits platelet functions ( fig. 3) [25]. However PKC activity was hardly affected.…”
Section: Signalling Metabolites and Platelet Pathologymentioning
confidence: 95%
“…Previously, our laboratory had shown that serine residues on the cytoplasmic domain of E-selectin became de-phosphorylated upon HL-60 adhesion (6). There have been reports that serine/threonine dephosphorylation may be involved in the subsequent tyrosine phosphorylation (35). We are in the process of determining whether cross-linking-induced dephosphorylation on serine residues is required for the observed phosphorylation on tyrosine residues in the cytoplasmic domain of E-selectin.…”
Section: Figmentioning
confidence: 99%